INFLUENCE OF DIFFERENT CONCENTRATION SUPLEMENTARY OF VITAMIN E IN YOLK EGG PHOSPHATE DILUENT FOR THE MOTILITY AND VIABILITY OF QUAIL SPERMATOZOA - Putra, I Made Hermadi; Bebas, Wayan; Budiasa, I Made Kota (Buletin Veteriner Udayana; Vol. 11 No. 1 Pebruari 2019, 2019)
This study aimed to determine influence of collecting frequency against concentration and spermatozoa abnormalities of quail. This study used a completely randomized design (CRD) with 3 treatment groups, is collecting sement at 2, 3 and 4 days intervals. Each treatment be repeated 9 times. Observations were made on the concentration of spermatozoa (107sel / ml) and abnormalities of spermatozoa (%). The data was analyzed using analysis of variance (ANOVA), if there are significantly different (P <0.05) followed by Duncan test. The results showed the concentration of spermatozoa in each treatment respectively 39.00 ± 5.148 x 107 cells / ml; 59.49 ± 1.878 x 107 cells / ml; 59.11 ± 2.028 x 107 cells / ml. Abnormality in each treatment was 14.22 ± 1.394%; 7.22 ± 1.202%; 7.49 ± 1.130%. The frequency of ejaculation was statistically significant (P <0.05) against the concentration and spermatozoa abnormalities of quail.